Trichomonas vaginalis and Mycoplasma genitalium: age-specific prevalence and disease burden in men attending a sexually transmitted infections clinic in Amsterdam, the Netherlands. (17th August 2015) - van der Veer, C; van Rooijen, M S; Himschoot, M; de Vries, H J C; Bruisten, S M
Abstract : Background: Men are not routinely tested for Trichomonas vaginalis (TV) and Mycoplasma genitalium (MG) in the Netherlands and, therefore, very few studies have looked into their prevalence and/or role in urogenital complaints in the Dutch male population. Objective: To describe the age-specific prevalence and disease burden of TV and MG, and their co-occurrence with Chlamydia trachomatis (CT), in men attending the sexually transmitted infections (STI) clinic in Amsterdam, the Netherlands. Methods: Urine samples and clinical data were collected from 526 men who have sex with women (MSW) and 678 men who have sex with men (MSM) attending the STI clinic. To investigate age as a risk factor, we oversampled older men. Urine samples were tested for TV and MG using molecular tests. Results: The overall prevalence was 0.5% (6/1204) for TV and 3.1% (37/1204) for MG. Four out of the six TV cases were older than 40 years and all TV cases were MSW. No age trend was observed for MG, nor did MG prevalence differ between MSW and MSM. Co-infections between TV or MG and CT were rare. TV infection did not associate with urogenital symptoms, whereas 5.9% of men reporting urogenital symptoms were infected with MG. Conclusions: TV infection was rare in men, asymptomatic and was limited to the heterosexual network. MG infection was relatively common and equally prevalent among MSW and MSM of all ages. Most MG infections remained asymptomatic, however, our results suggest that up to 6% of urogenital complaints could be explained by MG infection.